The management and disposal of clinical waste in government hospital / Nur Assyahiddah Yahya - Yahya, Nur Assyahiddah (Faculty of Architecture, Planning and Surveying, 2013)
The waste management is one of the main aspects in development country. Clinical waste, medical waste or health-care waste is the waste generated by health-care institution such as health care establishments, research facilities and laboratories. In August 2008, there are improper disposal of clinical waste by hospitals and health clinics. While on 31 July 2011, damages of incineration machine causes of dumping of clinical waste bag at Lembah Klang and east coast area. The dumping of clinical waste at incineration area causes bad smell and giving harm to worker and surrounded people due to release of dioxide gas. Scope of the research covers on study and understanding the process, identifying problems faces and recommending for improving the management and disposal of clinical waste in three different concession and government hospitals. The method of site visit, semi-structured interview and questionnaire distribution had been made. Literature research and additional data had been conducted to strengthen the research. Each concession had followed the guidelines on handling and management of clinical waste in Malaysia by Malaysia Environment Department. The system been used is same at all concession and minor different according to HSIP. The problem faces by each concession was different but it being agreed that awareness from hospital staff was main causes. The recommendation on improving supplying the consumable and receptacles and also frequent training will overcome the problems.